Efficacy of in vitro antimicrobial intracanal medicaments against C. albicans and E. faecalis in primary teeth - Emily Feitosa RÊGO; Yedda Maria Ribeiro Vasconcelos ROSÁRIO; Rogerio GLEISER; Antônio FERREIRA-PEREIRA; Maristela Barbosa PORTELA; Laura Guimarães PRIMO (Brazilian Oral Research)
Abstract To exclusively evaluate, in vitro, the efficacy of five intracanal medicaments against Candida albicans and Enterococcus faecalis in infected single-rooted primary teeth. Forty-three teeth were selected, out of which 42 were simultaneously contaminated with C. albicans and E. faecalis, verified by measuring the initial quantification (IQ), whereas one tooth was used as sterile control. Forty-two teeth were then randomly assigned to six groups (n = 7 teeth in each); one was the control group, while the others received calcium hydroxide (CH), camphorated paramonochlorophenol (CMCP), CH/CMCP, chlorhexidine (CHX), or iodoform paste (IP). Two samples from each group were then randomly selected and evaluated under a scanning electron microscope along with the sterile control (n = 1) for qualitative analyses (n = 13). The remaining samples (n = 30) were collected after 7 days of intracanal medicaments (final quantification - FQ) and 7 days after medicament removal (residual quantification – RQ). ANOVA and Tukey’s and c2 tests (p £ 0.05) were performed for the statistical analysis. All the medicaments, except CMCP, significantly reduced the levels of C. albicans from IQ to FQ (p = 0.046). Only CHX (p = 0.000) and IP (p = 0.007) showed a significant reduction from IQ to FQ against E. faecalis. The 2% CHX and IP demonstrated a favorable performance as an intracanal medicament, with a good antimicrobial activity against C. albicans and E. faecalis.